Lidové divadlo a masopust - Miriam Sudková Srncová (AntropoWebzin, 2011)
The text describes carnival rounds in Straz and Nevolice in the Lower Chodsko Region. The first part of the study is focused on description of czech middle-age carnival plays. The second part deals with the origins of the folk-theatre. The annual custom called Prahudky and related verbal, musical and dance rituals performed in the Chodsko Region are described in detail, and characteristic features of the folk-theatre and its difference from the classic theatre are explained. Prahudky is a restored local custom of celebrating an „inside out“ wedding, which is common for both villages. The girl dressed as a groom and the boy as a bride get married with the assistance of the priest, who is also the leader of the whole carnival round. Shrovetide and Prahudky represent an important part of social life of the inhabitants of  the Lower Chodsko Region.